Experimental study and numerical simulation of the cracking and failure performance for urban transportation hub slabs. (20th May 2021) - Li, Yu-Hang; Deng, Yang; Li, Ai-Qun
To investigate the cracking and failure performance of various forms for slabs, experimental studies on layered slabs and integral slabs under linear loading and cyclic incremental loading are carried out. The reliable numerical simulation based on the solid element is proposed and the reliability of the method is verified. The main three factors affecting cracking and failure performance of slab are calculated and analysed. The results show that the cracking and failure phenomenon and performance of the slabs with the layered slabs and integral slabs are different. The bearing capacity and mechanical performance of the integral slab are better than the layered slab. The slab cracking load, initial stiffness, and bearing capacity are affected by the slab thickness, the rebar ratio, and the proportion of the surface part, which need to be considered in the slab design.